Identification of Pineapple Fruit Rot Disease in Kubu Raya, West Borneo - Apindiati, Rita Kurnia; Hendarti, Indri; Rizal, Muhammad; Tarigasa, Odilo (Jurnal Biologi Tropis, 2025)
Pineapple productivity in West Borneo ranks second after bananas. One of the obstacles in pineapple cultivation is the presence of diseases that attack pineapple plantations. Symptoms of pineapple plant disease are an indication that the plant is attacked by pathogens. This study aims to identify pathogens that cause rot symptoms in pineapple fruit. The methods used in this study include surveys, survey evaluations, observation of symptoms in pineapple plantations, and laboratory tests of pathogens that cause pineapple fruit rot disease in Kubu Raya, West Borneo. Sampling was carried out by purposive sampling on pineapples with rot symptoms. Based on the results of the study obtained, it shows that the symptoms of pineapple fruit rot disease are characterized by the presence of soft rot that is blackish brown in color, rotten inside and emits a distinctive odor. Pineapple fruit rot is caused by the pathogens Curvularia sp. and Fusarium sp.